Coal saving in China: from Pareto-Koopmans to Kaldor-Hicks criterion. Issue 1 (12th February 2018) - Wang, Jianlin; Tian, Yi; Song, Malin; Zhao, Jiajia; Li, Hongzhou
Abstract : Purpose: In the creation of coal consumption reduction policy, the Chinese Government selected eight provinces as key provinces and encouraged them to replace coal with other non-coal energy, involving Kaldor-Hicks improvement. The purpose of this paper is to answer how much coal can be conserved if Kaldor-Hicks improvement is considered. Design/methodology/approach: A DEA model reflecting Kaldor-Hicks improvement is suggested to calculate the potential of coal reduction, and an endogenous directional distance function model is proposed to calculate the energy consumption efficiency. Findings: The results show that the non-key provinces wasted more coal than the key provinces, although the latter are of more concern. From the Kaldor-Hicks criterion, ten non-key provinces in a certain year can save more coal from an energy substitution policy and eight key provinces cannot. Through measurement of coal and energy efficiency, it is also found that provinces with an abundance of coal perform the worst in China. Originality/value: Previous studies measuring Chinese saving potential of coal mainly focused on Pareto-Koopmans criterion, not consistent to policy practices. This study changes to Kaldor-Hicks criterion, allowing to make some factors better off and other factors worse off.